Epidemiological and endoscopic profile of patients with upper gastrointestinal bleeding at a tertiary care center in Northern India : A retrospective analysis of twenty years - Shabir A Shiekh; Waseem Raja; Majid Khalil; Bilal A Khan; Showkat A Kadla (Asian Journal of Medical Sciences, 2023)
Background: Upper gastrointestinal (UGI) bleed is a common emergency presenting to emergency departments all over the world. Since the spectrum of UGI bleeding varies from region to region, it is important to know the profile of UGI bleed for proper management approach. Here, we present the endoscopic profile of UGI bleed presenting to a tertiary care setting in Northern India. Aims and Objectives: This study aimed to determine the epidemiological and endoscopic profile of patients with UGI over twenty years. Materials and Methods: The retrospective and observational study included adults patients (above 18 years of age) of either gender, who presented with UGI bleed at our center over a twenty year period from January 1999 to December 2018. Results: A total of 13418 patients with UGI bleed had esophagogastroduodenoscopy (EGD) done on them during this period. Six thousand one hundred and thirty-two patients (45.7%) were females while 7285 were males (54.3%). Mean age was 46±16 years. The common endoscopic findings were peptic ulcer disease in 7508 (48.25%) patients followed by erosive gastritis in 2305 (14.81%), UGI tract malignancy in 1152 (7.8%). Variceal bleed was seen in 900 (5.77%) patients. Conclusion: Peptic ulcer related bleed is the most common cause of UGI bleed in our center. Portal hypertension is relatively less frequent a cause of UGI bleed in our place.